The test of an improved jumbo windmill - Maelzer, V. (My University, 1897)
Introduction: The use of wind as a prime mover is a very ancient method of obtaining power. The large four vaned windmill of Holland has been embodied in literature just as the high majestic overshot waterwheel. Both are quite old. But age is not always a sign of development. Windmill construction has received quite an impetus in the last few years because of the increased demand for the utilization of wind power in the growing field of irrigation. Hence we see constant efforts being made to improve in order to get the greatest amount of power for the wind velocity and the size of the wheel. Here in Kansas the windmill is of special importance because, in the first place, we have the wind, and in the second place we have much need of just such a power for pumping water for stock and for irrigation purposes, for running feed grinders, etc. To meet this demand for improvement the resulting forms of wind motors have been numerous and the variety extends over a wide range. Even so much so that the uninitiated traveler in the sunflower state would not recognize many of the contrivances as belonging to the genus windmill. Probably the principal reason for the apparent success of all the types of wind engine is the difficulty of making a practical test of their relative merits.
Citation: Maelzer, V. The test of an improved jumbo windmill. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Windmill; Irrigation; Engineering; Theses; Manuscripts (documents)